2020
DOI: 10.3390/plants9020136
|View full text |Cite
|
Sign up to set email alerts
|

Role of Jasmonic Acid Pathway in Tomato Plant-Pseudomonas syringae Interaction

Abstract: The jasmonic acid pathway has been considered as the backbone of the response against necrotrophic pathogens. However, a hemi-biotrophic pathogen, such as Pseudomonas syringae, has taken advantage of the crosstalk between the different plant hormones in order to manipulate the responses for its own interest. Despite that, the way in which Pseudomonas syringae releases coronatine to activate jasmonic acid-derived responses and block the activation of salicylic acid-mediated responses is widely known. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
(64 reference statements)
3
5
0
Order By: Relevance
“…These authors studied the behavior of SiOPR3 transgenic plants (plants whose Opr3 gene has been silenced, disrupting the JA synthesis pathway at the OPDA level) on PstDC3000 infection at normal temperatures. They demonstrated that the reduction in the severity of bacterial disease was accompanied by an enhancement of OPDA levels, as well as reduced levels of JA and JA-Ile [55]. This proves the importance of this oxylipin in the response of tomato plants to Pseudomonas and confirmed our results, as we observed a synergic activation of the SA and JA pathways with an increase in PR1 expression and OPDA accumulation in T26 • C plants.…”
Section: Discussionsupporting
confidence: 90%
“…These authors studied the behavior of SiOPR3 transgenic plants (plants whose Opr3 gene has been silenced, disrupting the JA synthesis pathway at the OPDA level) on PstDC3000 infection at normal temperatures. They demonstrated that the reduction in the severity of bacterial disease was accompanied by an enhancement of OPDA levels, as well as reduced levels of JA and JA-Ile [55]. This proves the importance of this oxylipin in the response of tomato plants to Pseudomonas and confirmed our results, as we observed a synergic activation of the SA and JA pathways with an increase in PR1 expression and OPDA accumulation in T26 • C plants.…”
Section: Discussionsupporting
confidence: 90%
“…However, it is important to mention that different fine-tuned hormonal regulations could be observed depending on the pathogens’ lifestyle [ 33 , 34 ]. In contrast with fungi, the repression of JA and the activation of SA promoted the immune response in the R genotype to R. solanacerarum , confirming previous findings [ 35 , 36 ]. Differences in hormone regulation may also induce plants’ anti-herbivore characteristics [ 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…In concrete, the amount of this compound was significantly higher in young infected leaves of young plants than in all other samples (p < 0.01, Table 2). This observation is similar to that of Scalschi et al, who found increased amounts of salicylic acid in tomato 48 h after infection with P. syringae [28].…”
Section: Concentrations Of Selected Phenolic Acidssupporting
confidence: 92%